ANALISIS KECERDASAN LOGIS MATEMATIS KELAS 4 SEKOLAH DASAR PADA PENYELESAIAN SOAL CERITA PERKALIAN MATEMATIKA - Khurin Aini; Dyah Triwahyuningtyas; Nyamik Rahayu Sesanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Mathematical logical intelligence plays an important role in developing students' mathematical problem-solving abilities, especially in solving multiplication word problems at the elementary school level. This study aims to analyze the mathematical logical intelligence of fourth-grade students in solving multiplication word problems based on five indicators, namely mathematical calculations, logical thinking, problem solving, inductive and deductive estimation, and pattern and relationship intensity. This study uses a descriptive qualitative approach with data collection techniques in the form of written tests, observations, and interviews. The subjects consisted of three students representing the categories of high, medium, and low logical mathematical intelligence. The results showed that students with high intelligence were able to think systematically and recognize patterns consistently. Students with moderate intelligence can solve basic problems but have difficulty in developing systematic steps. Students with low intelligence show obstacles in all indicators, especially in converting verbal information into mathematical models. These findings indicate the importance of learning strategies tailored to students' cognitive profiles to improve their problem-solving competencies. This study contributes to the understanding of cognitive diversity in mathematics learning and has practical implications for teachers in designing more inclusive learning approaches.